2001
DOI: 10.1292/jvms.63.867
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Arthropathic Dose and Its Disposition Following Repeated Oral Administration of Ofloxacin, a New Quinolone Antimicrobial Agent, to Juvenile Dogs.

Abstract: ABSTRACT. A non-arthropathic dose and disposition of ofloxacin, a potent new quinolone antimicrobial agent, were assessed in male juvenile (3-month-old) dogs, when administered orally at 5, 10 and 20 mg/kg/day once daily for 8 consecutive days. Ofloxacin concentrations in sera and articular cartilages were analyzed by high-performance liquid chromatography (HPLC). Macroscopically, arthropathy characterized by fluid-filled vesicles in articular surface of the humerus and femur was observed in animals receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The range of concentrations tested (0.01 M-1.0 mM) in- cluded the peak plasma concentrations seen in humans with the four fluoroquinolones tested (5.6 -30 M after a single oral dose of 500 mg) and the highest concentrations observed in articular tissue (Meissner et al, 1990;Yabe et al, 2001). Recently, Yabe et al (2001) reported that intraarticular OFX concentrations in juvenile dogs were approximately 1.8 to 2.0 times higher than the serum concentration 2 h after dosing.…”
Section: Tenotoxicity and Tissue Diffusion Of Fluoroquinolonesmentioning
confidence: 82%
See 1 more Smart Citation
“…The range of concentrations tested (0.01 M-1.0 mM) in- cluded the peak plasma concentrations seen in humans with the four fluoroquinolones tested (5.6 -30 M after a single oral dose of 500 mg) and the highest concentrations observed in articular tissue (Meissner et al, 1990;Yabe et al, 2001). Recently, Yabe et al (2001) reported that intraarticular OFX concentrations in juvenile dogs were approximately 1.8 to 2.0 times higher than the serum concentration 2 h after dosing.…”
Section: Tenotoxicity and Tissue Diffusion Of Fluoroquinolonesmentioning
confidence: 82%
“…Recently, Yabe et al (2001) reported that intraarticular OFX concentrations in juvenile dogs were approximately 1.8 to 2.0 times higher than the serum concentration 2 h after dosing. Similarly, Meissner et al (1990) reported that halflife of OFX was longer in synovial tissues than in serum.…”
Section: Tenotoxicity and Tissue Diffusion Of Fluoroquinolonesmentioning
confidence: 99%
“…These doses may result in C max <10 μ g/mL ( c . 0.03 m m ) at most, based on their pharmacokinetics after oral administration as a single dose in dogs (Yabe et al. , 2001 for OXF Boothe et al.…”
Section: Discussionmentioning
confidence: 99%
“…That of NFX is 11-22 mg/kg/day. These doses may result in C max <10 lg/mL (c. 0.03 mM) at most, based on their pharmacokinetics after oral administration as a single dose in dogs (Yabe et al, 2001for OXF Boothe et al, 2002for EFX, Kay-Mugford et al, 2002for OBFX, Wallis et al, 1996. Although CFX is not used for animal therapy, it is detected in plasma as a metabolite of EFX, and its C max has been reported to be nearly 2 lg/mL (0.009 mM) after the highest dose of EFX (Boothe et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In juvenile animals, quinolone concentrations are generally higher in the articular cartilage than in plasma. The lowest arthropathogenic concentrations have been reported to be 20.6, 9.4 and 6.9 µg/g for norfloxacin and 34.1, 21.5 and 4.6 µg/g for nalidixic acid in juvenile rats, rabbits and dogs, respectively 7 ; 12.2 µg/g for levofloxacin in juvenile rabbits 51 ; and 8.7 µg/g for ofloxacin in juvenile dogs 67 . On the other hand, there is only very limited data for humans: the mean ofloxacin cartilage concentrations are 1.38, 2.19 and 2.18 kg/l (assuming an average bone density of 1.9 kg/l) at 98, 246 and 716 min after completion of 20 min infusion of 200 mg ofloxacin to 23 adult patients who underwent total hip replacement for osteoarthritis 68 .…”
Section: Osteochondrosismentioning
confidence: 99%